A HOLISTIC APPROACH TO LOWERING BLOOD PRESSURE - Julia Gawron; Łukasz Grajcarek; Anna Hamerla; Radosław Szydłowski; Magdalena Bodera; Hanna Porwolik; Agata Porwolik; Bartłomiej Czarnecki; Anna Kaźmierska; Bartosz Tadeusiak (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Hypertension affects over 1.28 billion adults worldwide and is a leading global health concern due to its strong association with heart disease, stroke, and other complications, with nearly half of affected individuals unaware of their condition. Effective management strategies, including the promotion of sports activities to lower blood pressure, are essential to reduce the significant health risks and disease burden linked to high systolic blood pressure. The aim of the work is to present the latest reports on lowering blood pressure through sports activities. Material and methods: For this work, we conducted a search in January 2025 in the PubMed and Google Scholar databases using the keywords: "blood pressure," "sport," "hypertension," followed by an analysis of the selected materials. Aim of the study: The aim of the work is to present the latest reports on lowering blood pressure through sports activities. Conclusion: The integration of diverse exercise modalities, such as isometric exercise training, sprint interval training, moderate-intensity continuous training and tai chi into public health strategies could significantly enhance hypertension management. Only five minutes of training a day can result in blood pressure reduction and can benefit patients with hypertension.